The role of forests as carbon sinks: Land-use and carbon accounting - Renato Rosa; Clara Costa Duarte; Maria A. Cunha-e-Sá (Fondazione Eni Enrico Mattei (FEEM), 2009)
The use of forests as carbon sinks is examined by introducing carbon sequestration benefits' accounting in a multi-vintage land allocation model. Following the IPCC, three carbon accounting methods are considered. We compare the results in each case with those without carbon sequestration, as well as the performances of the ton-year and the average methods (second-best) to the carbon flow (first-best) concerning optimal land allocation between forestry and alternative uses, total carbon sequestered, timber production and social welfare. A full proof of long-run optimality of steady state forest is provided. Numerical simulations are performed and results discussed illustrating the setup's potential.
Keywords: Q15; Q23; 330; Land Allocation Model; Forest Vintages; Carbon Sequestration; Carbon Accounting; Optimal Rotation; Transition/steady-state